2022
DOI: 10.1002/jmri.28451
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Dependent Changes in Knee Cartilage T1, T2, and T1pSimultaneously Measured Using MRI Fingerprinting

Abstract: Background Magnetic resonance fingerprinting (MRF) techniques have been recently described for simultaneous multiparameter cartilage mapping of the knee although investigation of their ability to detect early cartilage degeneration remains limited. Purpose To investigate age‐dependent changes in knee cartilage T1, T2, and T1p relaxation times measured using a three‐dimensional (3D) MRF sequence in healthy volunteers. Study Type Prospective. Subjects The study group consisted of 24 healthy asymptomatic human vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The experiments showed excellent repeatability of PD, T 1 , T 2 , T 1ρ , and B 1 parameter estimations. The same group investigated the age‐dependent changes of knee cartilage using a 3D MRF sequence for T 1 , T 2 , and T 1ρ maps in healthy subjects 89 . Higher global and regional cartilage T 2 and T 1ρ measurements were found for higher age groups as shown in Fig.…”
Section: Emerging Methods For Quantitative Mri For Cartilagementioning
confidence: 98%
See 1 more Smart Citation
“…The experiments showed excellent repeatability of PD, T 1 , T 2 , T 1ρ , and B 1 parameter estimations. The same group investigated the age‐dependent changes of knee cartilage using a 3D MRF sequence for T 1 , T 2 , and T 1ρ maps in healthy subjects 89 . Higher global and regional cartilage T 2 and T 1ρ measurements were found for higher age groups as shown in Fig.…”
Section: Emerging Methods For Quantitative Mri For Cartilagementioning
confidence: 98%
“…(a) Boxplot of cartilage T 1 , T 2 , and T 1ρ values for the different age groups, (b) illustrative cartilage proton density (PD), T 1 , T 2 , and T 1ρ maps of the lateral cartilage 89 . LFC‐lateral femoral cartilage, LTC lateral tibial cartilage, MFC‐medial femoral cartilage, MTC‐medial tibial cartilage, PC‐patellar cartilage.…”
Section: Emerging Methods For Quantitative Mri For Cartilagementioning
confidence: 99%
“…This work demonstrated the use of 3D‐MRF to understand the natural variation of knee cartilage relaxation parameters with age and gender in a cohort of healthy individuals 9 . Results demonstrated that there are age‐related changes in T 1 , T 2 , and T 1 rho relaxation within knee cartilage, possibly due to proteoglycan and cartilage matrix composition changes with natural aging.…”
mentioning
confidence: 84%
“…Preliminary clinical work in MRF on cartilage imaging has included using 3D MRF to quantify age-dependent differences in medial tibial and femoral cartilage between healthy patients and patients with knee osteoarthritis 177,178 . Quantification of hip cartilage using MRF has also been explored, with Sharafi et al 179 able to successfully characterize subregions of hip cartilage in both hips with excellent repeatability.…”
Section: Current Clinical Applicationsmentioning
confidence: 99%
“…176 Preliminary clinical work in MRF on cartilage imaging has included using 3D MRF to quantify age-dependent differences in medial tibial and femoral cartilage between healthy patients and patients with knee osteoarthritis. 177,178 Quantification of hip cartilage using MRF has also been explored, with Sharafi et al 179 able to successfully characterize subregions of hip cartilage in both hips with excellent repeatability. Cloos et al 180 were able to use MRF to enable semiautomatic hip cartilage segmentation and for T1/T2/proton density quantitative mapping, enabling an efficient and highly reproducible workflow for quantitative hip cartilage assessment.…”
Section: Musculoskeletal Applicationsmentioning
confidence: 99%